IDENTIFICATION OF SELF IN MEENA ALEXANDER’S ILLITERATE HEART - Banerjee, Priyanka (International Journal of Research -GRANTHAALAYAH, 2025)
Meena Alexander is a towering figure in the area of Indian English literature. She has attained popularity by dwelling upon the themes of space and dislocation in her poems. She has created great works of literature by speaking of her intense feelings of loneliness, homesickness, nostalgia and remembrance. One of her most acclaimed works is a collection of poems called Illiterate Heart for which she was even awarded the PEN Open Book Award in the year 2002. The book has sophistically touched the journey of a women through colonial and patriarchal didactics. Meena Alexander has vividly illustrated her the formation of a feminine language to expose the painful disconnection between the body and the soul. Alexander has even persisted upon the plight of the Indians during the Post colonial period and has reflected upon her memorable experiences of her childhood in India. The book has historical references of various freedom movements that had led India to her Independence in the year 1947. This research paper has tried to identify the various aspects of the major poems of the book that has made Meena Alexander as a poet par excellence and has created an urge in every reader to go back to one’s own native place and being surrounded by their near and dear one’s.